Combined small cell lung carcinoma harboring ALK rearrangement: A case report and literature review. Issue 12 (25th October 2020) - Niitsu, Takayuki; Shiroyama, Takayuki; Miyake, Kotaro; Noda, Yoshimi; Kido, Kansuke; Hara, Reina; Enomoto, Takatoshi; Adachi, Yuichi; Amiya, Saori; Suga, Yasuhiko; Fukushima, Kiyoharu; Koyama, Shohei; et al.
Abstract : Combined small cell lung cancer (c‐SCLC) is a relatively rare subtype of SCLC and is defined by the combination of SCLC and any elements of non‐small cell carcinoma (NSCLC). Standard chemotherapy for patients with c‐SCLC has not yet been established. Gene mutations such as epidermal growth factor receptor (EGFR) mutations may be detected in patients with c‐SCLC. However, little is known about anaplastic lymphoma kinase (ALK) rearrangement in c‐SCLC patients. Here, we report a young female patient who was successfully treated with alectinib for ALK‐positive c‐SCLC after failure of immunochemotherapy for SCLC and cytotoxic chemotherapy for adenocarcinoma. Moreover, we performed a literature review of EGFR‐ or ALK‐positive c‐SCLC patients. Our report suggests that ALK testing may be justified in patients with SCLC that contain an adenocarcinoma component. Key points: Significant findings of the study:  This is the first report describing the treatment course comprising immunochemotherapy and ALK‐TKI in a patient with c‐SCLC harboring ALK rearrangement. What this study adds:  Our case and literature review suggest that although ALK mutation is rare in patients with c‐SCLC, its identification and treatment with ALK‐TKIs may contribute to clinical benefits. Abstract : Standard chemotherapy for patients with c‐SCLC has not yet been established. Here, we report a young female patient successfully treated with alectinib for ALK‐positive c‐SCLC after failure of immunochemotherapy for SCLC and cytotoxic chemotherapy for adenocarcinoma.